RELATIONSHIP BETWEEN PRINCIPAL’S LEADERSHIP ROLE, SUBORDINATE MATURITY AND WORK MOTIVATION TOWARDS TEACHER’S DISCIPLINE - Nisa, Khoiru; Aslamiah; Suhaimi (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this study was to describe and analyze the indirect/direct role of the principal's leadership, subordinate maturity, work motivation, and discipline of teachers. This was a quantitative research with a correlational descriptive design. Data were obtained from 154 people through questionnaires. Furthermore, the data obtained were analyzed to test hypotheses using path analysis with multiple regression methods. The results showed that the Principal's indirect/direct Leadership Role, Subordinate Maturity, work motivation, and work discipline of teachers are in the moderate category. Efforts should be made to increase the level of maturity of subordinates, this can be done by involving low and middle-level teachers in various development programs, such as education and training, seminars, or if it is possible to provide learning tasks to teachers with low and moderate levels of maturity for raise the level of education to increase the maturity of their work